Improved inclination correction method applied to the guidance system of agricultural vehicles - Ospina, Ricardo; Noguchi, Noboru (International Journal of Agricultural and Biological Engineering, 2020)
This research introduces a new inclination correction method with increased accuracy applied to the guidance system of an agricultural vehicle. The method considers the geometry of a robot tractor and uses an Inertial Measurement Unit (IMU) to correct the lateral error of the RTK-GPS antenna measurements raised by the tractor’s inclinations. A parameters optimization experiment and an automatic guidance experiment under real working conditions were used to compare the accuracy of a traditional correction method with the new correction method, by calculating the RMSE of the lateral error and the error reduction percentage. An additional tuned correction method was found by using a simple analytical method to find the optimal variables that reduced the lateral error to a minimum. The results indicate that the new correction method and the tuned correction method display a significant error reduction percentage compared to the traditional correction method. The methods could correct the GPS lateral error caused by the roll inclinations in real-time. The resulting lateral deviation caused by the tractor’s inclinations could be reduced up to 23% for typical travelling speeds. Keywords: inclination correction method, guidance system, agricultural vehicles, robot tractor, IMU, RTK-GPS, precision farming DOI: 10.25165/j.ijabe.20201306.6012 Citation: Ospina R, Noguchi N. Improved inclination correction method applied to the guidance system of agricultural vehicles. Int J Agric & Biol Eng, 2020; 13(6): 183–194.